Producción y comercialización de frutas deshidratadas para exportación - Anda Benítez, María Gabriela (2010)
The present market was researched in order to know how possible and profitable can be to undertake a company dedicated to produce and commercialize dehydrated fruits for exporting. Through the study, it was determined that there is a good product acceptance in Europe, especially in Belgium, which offers a good price for imports and entry facilities into the European market. The organization will use the same commercial name as its brand in order to obtain a better recognition in the market. Throughout the research it was seen that there are the necessary means and resources to implement this business. lt is required an initial investment of USD 100.400,00. The most appropriate place for the location of this company is The Province of Santo Domingo; nevertheless, the offices will be in Guayaquil, to facilitate the administration and selling process. The Organization expects to be able to count with qualified human resource well-trained according to their function and ready to offer an excellent service. The result gotten from a financial study confirmed the viability of the project and revealed the convenience of appealing to a credit.